Escalas concorrentes para mensura????o do envolvimento: um estudo aplicado aos consumidores e praticantes de corrida de rua na cidade de S??o Paulo - Santos, Luiz Silva dos (2016)
The main objective of this work is to determine which of the two main constructs available in the marketing literature on the involvement of consumers (PII Personal Involvement Inventory - Zaichkowsky - 1994) and (NIP New involment Profile - Jain and Srinivasan - 1990), has the greatest power prediction as to word of mouth and repurchase intention to participate in street racing events in the city of S??o Paulo. The street race has shown an exponential increase in the number of practitioners every year in the same proportion also increases the number of events related to this sport practice, showing its importance as a promoter in the act of consumption, health and well-being of the population . Moreover, it is a popular sport low cost, low risk, high efficiency and great practicality. With this growth, the market has simultaneously attracting more competition between companies that organize these events in S??o Paulo, generating new challenges so that we can provide participants with a greater range of products and services to be offered to such customers and street runners, who are increasingly involved with this sport. Data were collected through a field survey with a sample of 320 respondents. To analyze the data we used structural equation modeling technique where it was found that construct NIP New involment Profile, it showed the best predictive results in relation to the mouth of variables mouth and repurchase intention. With the results obtained in this study is expected to increase knowledge of consumer involvement with sports and can be used by researchers and professionals of marketing and sport management.